2010
DOI: 10.1186/1477-7525-8-72
|View full text |Cite
|
Sign up to set email alerts
|

How do children at special schools and their parents perceive their HRQoL compared to children at open schools?

Abstract: BackgroundThere has been some debate in the past as to who should determine values for different health states for economic evaluation. The aim of this study was to compare the Health Related Quality of Life (HRQoL) in children attending open schools (OS) and children with disabilities attending a special school (SS) and their parents in Cape Town South Africa.MethodsThe EQ-5D-Y and a proxy version were administered to the children and their parents were requested to fill in the EQ-5D-Y proxy version without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 22 publications
2
33
0
5
Order By: Relevance
“…This is in agreement with previous studies comparing children with disabilities and typical children (Edwards et al, 2003;Gkoltsiou et al, 2008;Ikeda et al, 2014;Watson & Keith, 2002;Zwicker et al, 2013). In contrast, our results, do not confirm previous studies, which concluded that, despite any differences in the physical functioning domain, children with disabilities display similar or even better HRQOL scores compared with typical children (Albrecht & Devlieger, 1999;Jelsma & Ramma, 2010;Ju et al, 2006;King et al, 1993;Wendelborg & Tøssebro, 2011). Of the above, two studies have been performed in school settings.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…This is in agreement with previous studies comparing children with disabilities and typical children (Edwards et al, 2003;Gkoltsiou et al, 2008;Ikeda et al, 2014;Watson & Keith, 2002;Zwicker et al, 2013). In contrast, our results, do not confirm previous studies, which concluded that, despite any differences in the physical functioning domain, children with disabilities display similar or even better HRQOL scores compared with typical children (Albrecht & Devlieger, 1999;Jelsma & Ramma, 2010;Ju et al, 2006;King et al, 1993;Wendelborg & Tøssebro, 2011). Of the above, two studies have been performed in school settings.…”
Section: Discussionsupporting
confidence: 47%
“…First, some studies examined children with various physical disabilities (Ju et al, 2006;Watson & Keith, 2002), intellectual disabilities (Ikeda et al, 2014;Zwicker et al, 2013) or both (present study; Edwards et al, 2003) while one study examined students with chronic illnesses without providing specific information regarding the type or the severity of the illness (Gkoltsiou et al, 2008). Second, the use of the parent-proxy version of the questionnaire might have resulted in lower HRQOL scores than those reported by the children themselves (Achenbach, McConaughy, & Howell, 1987;Jelsma & Ramma, 2010). However, using self-report measures, some researchers have reported differences between those two groups (Edwards et al, 2003;Ikeda et al, 2014;Watson & Keith, 2002;Zwicker et al, 2013) but others have found the opposite (Jelsma & Ramma, 2010;Ju et al, 2006;King et al, 1993).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations